Acute Targeting of General Transcription Factor IIB Restricts Cardiac Hypertrophy via Selective Inhibition of Gene Transcription. (January 2015) - Sayed, Danish; Yang, Zhi; He, Minzhen; Pfleger, Jessica M.; Abdellatif, Maha
<x xml:space="preserve">Abstract</x> Background— We previously reported that specialized and housekeeping genes are differentially regulated via de novo recruitment and pause-release of RNA polymerase II, respectively, during cardiac hypertrophy. However, the significance of this finding remains to be examined. Therefore, the purpose of this study was to determine the mechanisms that differentially regulate these gene groups and exploit them for therapeutic targeting. Methods and Results— Here, we show that general transcription factor IIB (TFIIB) and cyclin-dependent kinase 9 are upregulated during hypertrophy, both targeted by microRNA-1, and play preferential roles in regulating those 2 groups of genes. Chromatin immunoprecipitation-sequencing reveals that TFIIB is constitutively bound to all paused, housekeeping, promoters, whereas de novo recruitment of TFIIB and polymerase II is required for specialized genes that are induced during hypertrophy. We exploited this dichotomy to acutely inhibit induction of the latter set, which encompasses cardiomyopathy, immune reaction, and extracellular matrix genes, using locked nucleic acid–modified antisense TFIIB oligonucleotide treatment. This resulted in suppression of all specialized genes, while sparing the housekeeping ones, and, thus, attenuated pathological hypertrophy. Conclusions— The data for the first time reveal distinct general TFIIB dynamics that regulate specialized versus housekeeping genes during cardiac hypertrophy. Thus, by acutely targeting TFIIB, we were able to inhibit selectively the former set of genes and ameliorate pressure overload hypertrophy. We also demonstrate the feasibility of acutely and reversibly targeting cardiac mRNA for therapeutic purposes using locked nucleic acid–modified antisense oligonucleotides.